Context effect and confirmation bias in criminal fact finding. (17th April 2020) - Rassin, Eric
Abstract : Purpose: Fact finding is an important part of the job of criminal trial judges and juries. In the literature, several potential pitfalls hindering fact finding have been identified, such as context effects (i.e. an unintended effect of non‐probative information on conviction) and confirmation bias (i.e. a skewed selection of and overreliance on guilt‐confirming evidence and neglect of exonerating information). In the present study, the effect of irrelevant contextual information on conviction and subsequent confirmation bias was tested. Method: A sample of Dutch professional criminal trial judges ( N = 105) studied a case file and decided on their conviction of the suspect's guilt, and subsequent investigation endeavours. There were two versions of the file, differing in non‐probative details that might affect conviction, such as crime severity and facial appearance of the suspect. Results: Findings suggest that context information indeed affected conviction, and the subsequent preference for guilt‐confirming investigation endeavours. Conclusion: Professional judges may be susceptible to bias threatening the objectivity of legal decision‐making.